Molecular Mechanisms of Tumor Cell Resistance to Chemotherapy Targeted Therapies to Reverse Resistance - Bonavida, Benjamin (Resistance to Targeted Anti-Cancer Therapeutics,, 2013)
Patients with various cancers are treated with conventional chemotherapeutic drugs and the majority responds well to such therapies. However, there is a subset of patients who does not respond initially and another subset who no longer responds to further treatments. Clearly, in those two subsets of patients, the cancer cells exhibit mechanisms of resistance. One of the main challenges facing us to date is to develop new therapies to treat patients with the resistant tumors. The development of new effective therapies will be dependent on delineating the biochemical, molecular, and genetic mechanisms that regulate tumor cell resistance. Such mechanisms have revealed gene products that directly regulate resistance and are targets for therapy. Of interest, several FDA-approved drugs were able to overcome drug resistance and have been successfully used clinically. They have been used as monotherapy or synergized with other therapies for the treatment of resistant tumors. This volume constitutes a total of twelve selective reviews by pioneer scientists in the field of cancer drug resistance. Specific mechanisms in drug resistance are reviewed and novel approaches are being proposed for therapeutic interventions. This volume is of general interest to scientists, clinicians, health care providers, and students.